The effect of noise stress on the serum testosterone level in spraque dawley rats - Chandralekha, G. (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Noise is a stress. Stress results in wide range of physiological responses in the body including the endocinological and reproductive functions. Only few studies evaluate the noise induced changes in the hormonal levels of rats and the results reported for correlation with the structural changes in the testis. I have evaluated the impact of noise stress on the testosterone hormone . There were nine groups. Acute group was exposed to one hour and three hours noise of 1 00 dB of traffic noise. The chronic group has group a which has one hour exposure to 60days and one hour exposure to 90 days. The chronic group B has three hours of exposure to 60 days and 90 days. All have control. Each group has 6 rats. After the stipulated time of exposure I the blood was collected for testosterone estimation and tissues like testis were collected. Testis was fixed in paraffin and sectioned and stained and observed for histopathological changes. Changes were noted in the testicular tubules and it is correlated with the decresed testosterone levels after exposure to noise stress. These changes differ from those reported earlier suggesting distinct adaptation potential in stressful condition .